Moderasi beragama sebagai strategi kebangsaan: perspektif islam wasathiyyah dan implementasinya dalam pendidikan multikultural - annadwi, FadlilM Fadlil Afi Annadwi Agiafi (Maliki Interdisciplinary Journal, 2026)
Indonesia is a country with a very high level of diversity, in terms of religion, ethnicity, culture, language, and tradition. This diversity is both a wealth and a challenge in the life of the nation, especially when differences are not managed wisely and fairly. The phenomena of intolerance, radicalism, and exclusive religious attitudes that are sometimes found in various layers of society highlight the importance of a religious paradigm that can maintain unity and social harmony. In this context, religious moderation emerges as a concept and strategy that demands fairness, balance, and proportionality in understanding and practicing religious teachings. This article aims to examine religious moderation as a concept and practice, viewed from the perspective of Islamic wasathiyyah, its relevance in the context of Indonesian nationalism, and its implementation through education, particularly in a multicultural educational environment. The method used in this study is a literature review by examining various relevant sources related to religious moderation, Islamic education, and multicultural education. The results of the review show that religious moderation has a strong theological basis in Islam through the principle of wasathiyyah, which emphasizes the values of justice, balance, and tolerance. In the national context, religious moderation plays a role as a link between religious commitment and national commitment, thereby strengthening national integration. The implementation of religious moderation through education has proven effective in shaping students' characters to be tolerant, inclusive, and non-violent, as well as contributing to preventing the development of radicalism and intolerance among young people.